2022
DOI: 10.3389/fimmu.2022.1046352
|View full text |Cite
|
Sign up to set email alerts
|

Risk of COVID-19 infection, hospitalization and mortality in psoriasis patients treated with interleukin-17 inhibitors: A systematic review and meta-analysis

Abstract: BackgroundCoronavirus disease 2019 (COVID-19) have brought great disaster to mankind, and there is currently no globally recognized specific drug or treatment. Severe COVID-19 may trigger a cytokine storm, manifested by increased levels of cytokines including interleukin-17 (IL-17), so a new strategy to treat COVID-19 may be to use existing IL-17 inhibitors, which have demonstrated efficacy, safety and tolerability in the treatment of psoriasis. However, the use of IL-17 inhibitors in patients with psoriasis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Immune pathways associated with the pathogenesis of psoriasis and the drugs used to treat psoriasis may have a differential impact on the clinical course of COVID-19.The IL-23/Th17 axis has a central role in the pathogenesis of psoriasis, while plasmacytoid DCs are involved via IL-36 signalling and type I interferon activation[8].In the initial phase of COVID-19, when early host type I IFN-mediated inhibition of viral replication is essential, immune dysregulation in psoriasis may be bene cial while immunosuppressive drugs may be detrimental [9].However, biologics are more targeted to inhibit an in ammatory factor and less involved in the components of the viral immune response mentioned earlier [10].Trials also suggested that the use of biologics (TNF-α, IL-17 and IL-23 inhibitors) in psoriasis is not associated with increased rates of viral infections such as in uenza compared to placebo [11].Some studies have found that the use of IL-17 inhibitors in patients with psoriasis does not increase the risk of SARS-CoV-2 infection or worsen the course of neocoronary pneumonia compared to the use of nonbiologics [12].One study analyzed skin tissue from psoriasis patients before and after treatment with IL-17 monoclonal antibodies and found decreased expression of ACE2 (a receptor necessary for cells infected with COVID-19) in patient lesions, suggesting that IL-17 antibodies may reduce the risk of COVID-19 by reducing cells that interact with SARS-CoV-2.The results of this study suggest that IL-17 monotherapy does not increase the risk of COVID-19 infection, but rather controls in ammation while downregulating ACE2 and thereby decreasing the risk of infection [13].…”
Section: Discussionmentioning
confidence: 96%
“…Immune pathways associated with the pathogenesis of psoriasis and the drugs used to treat psoriasis may have a differential impact on the clinical course of COVID-19.The IL-23/Th17 axis has a central role in the pathogenesis of psoriasis, while plasmacytoid DCs are involved via IL-36 signalling and type I interferon activation[8].In the initial phase of COVID-19, when early host type I IFN-mediated inhibition of viral replication is essential, immune dysregulation in psoriasis may be bene cial while immunosuppressive drugs may be detrimental [9].However, biologics are more targeted to inhibit an in ammatory factor and less involved in the components of the viral immune response mentioned earlier [10].Trials also suggested that the use of biologics (TNF-α, IL-17 and IL-23 inhibitors) in psoriasis is not associated with increased rates of viral infections such as in uenza compared to placebo [11].Some studies have found that the use of IL-17 inhibitors in patients with psoriasis does not increase the risk of SARS-CoV-2 infection or worsen the course of neocoronary pneumonia compared to the use of nonbiologics [12].One study analyzed skin tissue from psoriasis patients before and after treatment with IL-17 monoclonal antibodies and found decreased expression of ACE2 (a receptor necessary for cells infected with COVID-19) in patient lesions, suggesting that IL-17 antibodies may reduce the risk of COVID-19 by reducing cells that interact with SARS-CoV-2.The results of this study suggest that IL-17 monotherapy does not increase the risk of COVID-19 infection, but rather controls in ammation while downregulating ACE2 and thereby decreasing the risk of infection [13].…”
Section: Discussionmentioning
confidence: 96%
“…Gargiulo et al reported a case series which supported the use of biologics in psoriasis patients with short disease duration and emphasized the safety of these treatments during the COVID‐19 pandemic 5 . Several studies have shown that the levels of circulating IL‐17 are elevated in the peripheral blood of COVID‐19 patients, which provided evidence to support treatment decisions for psoriasis patients treated with IL‐17 inhibitors during the COVID‐19 pandemic 6 . That may also account for the mild symptoms of COVID‐19 infection in our patient when using the treatment of secukinumab.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that the use of IL-17 inhibitors, including SEC, IXE, and brodalumab in patients with psoriasis does not increase the risk of SARS-CoV-2 infection or worsen the course of COVID-19 [ 21 , 22 ]. In addition, IXE, SEC, and brodalumab can reduce the mRNA level of SARS-CoV-2 receptor ACE2 in skin lesions of patients with psoriasis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%